2018
DOI: 10.1371/journal.pone.0207041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin exposure on growth and photosynthetic performance in the unicellular freshwater chlorophyte, Chlorella vulgaris

Abstract: Many pharmaceuticals have negative effects on biota when released into the environment. For example, recent work has shown that the commonly prescribed antidiabetic drug, metformin (N,N-dimethylbiguanide), has endocrine disrupting effects on fish. However, effects of metformin on aquatic primary producers are poorly known. We exposed cultured isolates of a freshwater chlorophyte, Chlorella vulgaris, to a range of metformin concentrations (0–767.9 mg L-1) to test the hypothesis that exposure negatively affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Under the stress of PA and GA, the PSII activity of M. aeruginosa was influenced at the beginning, but non-photochemical quenching could protect the photosynthesis (Sonani et al, 2018). The protective effects of non-photochemical quenching were gradually lost for further inhibition, and photochemical quenching parameters decreased followly, ultimatly, photosynthetic efficiency dropped significantly (Cummings et al, 2018). For instance, the expression of psbA gene encoding the stress-adapting D1 protein (the main components of PSII) was inhibited by PA in cyanobacteria Cylindrospermopsis raciborskii (Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the stress of PA and GA, the PSII activity of M. aeruginosa was influenced at the beginning, but non-photochemical quenching could protect the photosynthesis (Sonani et al, 2018). The protective effects of non-photochemical quenching were gradually lost for further inhibition, and photochemical quenching parameters decreased followly, ultimatly, photosynthetic efficiency dropped significantly (Cummings et al, 2018). For instance, the expression of psbA gene encoding the stress-adapting D1 protein (the main components of PSII) was inhibited by PA in cyanobacteria Cylindrospermopsis raciborskii (Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The excess light energy is eliminated by non-photochemical quenching to protect the normal progress of the photochemical reaction (Yong et al, 2018). Therefore, non-photochemical quenching parameters always increase to protect photosynthesis under mild stress or in the early stage of severe stress by quenching (e.g., pH-gradient build-up, LHC 2 phosphorylation and zeaxanthin formation) and recovery (such as a stressadapting D1 protein) mechanisms, but decrease with further damage (Cummings et al, 2018;Nowicka, 2019). Photochemical quenching parameters reflect the photochemical capacity of PSII in the light-adapted state and correspond to the steady-state fraction of oxidized PSII reaction centers (Zulfugarov et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These products also cause endocrine disruption in reproductive tissues of fishes, leading to the development of intersex gonads in males, and reduction of fecundity in treated pairs of fishes (Niemuth and Klaper, 2015). Some negative effects of Metformin on photosynthetic activity of the freshwater chlorophyte, Chlorella vulgaris have also been reported (Cummings et al, 2018). Nevertheless, another study revealed no physiological consequence on the health of a freshwater gastropod -the big ramshorn snail (Planorbarius corneus) -due to an exposition to Metformin and to its transformed product guanylurea at environmentally relevant concentrations (Jacob et al, 2019).…”
Section: Metformin the Second More Frequent Polluting Api In Freshwat...mentioning
confidence: 99%
“…Metformin has been observed in a vast array of natural waterways, with concentrations often linked to the number of metformin prescriptions in a given area (Oosterhuis et al, 2013;Wilkinson et al, 2022). It has been reported in wastewater systems in a number of countries, including Germany, Canada, the United States, Greece, The Netherlands, and China (Blair et al, 2013;Bradley et al, 2020;Cummings et al, 2018;Kosma et al, 2014;Oosterhuis et al, 2013;Scheurer et al, 2012;Tao et al, 2018;Trautwein & Kümmerer, 2011;Yao et al, 2018). Concentrations of metformin in the environment vary greatly but have been reported to range from 41 to 123 µg/L in WWTP effluent in Hamilton, Ontario, Canada (Parrott et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Both metformin and guanylurea have documented ecotoxicological implications (Cummings et al, 2018; Magnoni et al, 2012; Oosterhuis et al, 2013; ter Laak et al, 2014; Yao et al, 2018). The predicted‐no‐effect concentrations have been reported to be 1 mg/L for metformin and 0.16 mg/L for guanylurea (Caldwell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%